Disruption of Atg7-dependent autophagy causes electromotility disturbances, outer hair cell loss, and deafness in mice - Zhou, Han (Cell Death Dis, 2020)
Atg7 is an indispensable factor that plays a role in canonical nonselective autophagy. Here we show that genetic ablation of Atg7 in outer hair cells (OHCs) in mice caused stereocilium damage, somatic electromotility disturbances, and presynaptic ribbon degeneration over time, which led to the gradual wholesale loss of OHCs and subsequent early-onset profound hearing loss. Impaired autophagy disrupted OHC mitochondrial function and triggered the accumulation of dysfunctional mitochondria that would otherwise be eliminated in a timely manner. Atg7-independent autophagy/mitophagy processes could not compensate for Atg7 deficiency and failed to rescue the terminally differentiated, non-proliferating OHCs. Our results show that OHCs orchestrate intricate nonselective and selective autophagic/mitophagy pathways working in concert to maintain cellular homeostasis. Overall, our results demonstrate that Atg7-dependent autophagy plays a pivotal cytoprotective role in preserving OHCs and maintaining hearing function.